Inclusive Growth Stimulation in Underserved Communities through Digital Micro Entrepreneurship Programs - Maulana Agung Wibowo; Tatik Mariyanti; Mardiana Mardiana; Ester Ananda Natalia; Yasir Mustafa Kareem (ADI Bisnis Digital Interdisiplin Jurnal, 2025)
The rapid development of the digital economy has intensified consumer interactions with businesses through digital platforms. This condition highlights the urgency of implementing digital business ethics, including transparency in privacy policies, honesty in marketing communication, data protection, and fair algorithmic practices, as key factors in building consumer trust. This paper examines the relationship between digital business ethical practices and consumer trust levels through a review of empirical and conceptual literature (2021–2025). The synthesis indicates that clear ethical practices (transparency, data security, information accuracy, and AI accountability) enhance both emotional and cognitive consumer trust, which in turn strengthens repurchase intention and loyalty. Practical implications and future research directions are provided.